Media transition and social exclusion: Structural poverty in the Gadukan community post digital television migration - Ranta Amina, Nurtyasih Wibawanti; Sadono, Teguh Priyo (Bricolage : Jurnal Magister Ilmu Komunikasi, 2026)
The Ministry of Communication and Information Technology Regulation No. 07/P/M KOMINFO/3/2007, which marked the beginning of television digitization, compelled people to switch from analog to digital.  The acquisition of a set-top box (STB) was necessary for this relocation.  Due to the lack of STB (television station) coverage, a slum area in Gadukan village, North Surabaya, has trouble viewing television; as a result, they lose their sources of knowledge and amusement.  The flood of information and entertainment around them marginalizes the locals.  Inequality in the slum community will be made worse by this circumstance.  Research on how people feel excluded from enjoyment and information is based on this. The central thesis of the notion of technological determinism is that human existence itself will be shaped by changes in communication methods.  According to Valente's Theory of Innovation Diffusion, social networks can affect the rate and pattern of innovation diffusion; being in the center of the social network and having a large number of social connections tend to be quicker and more efficient.  According to Robert K. Merton's strain theory, imbalance brought on by marginalization increases a person's susceptibility to pressure that results in abnormal behavior. Phenomenological studies were employed as part of the qualitative research methodology.  The findings demonstrate how poor groups' access to information has been marginalized as a result of television's digital migration.  The idea that media technological determinism is a structural tool in poverty has been reinforced by poverty resulting from information marginalization.